Behavioral and clinical aspects associated with probable sleep bruxism in early childhood - Caio André da Silva EMÍDIO; Luiz Felipe Nogueira SANTOS; Diego Patrik Alves CARNEIRO; Patrícia Rafaela dos SANTOS; Silvia Amélia Scudeler VEDOVELLO; Heloisa Cristina VALDRIGHI (Universidade Estadual Paulista, 2020)
Abstract Introduction Although many studies are being carried out with sleep bruxism, the literature points to a lack of studies with methodological quality in children. Objective To evaluate the behavioral and clinical aspects associated with probable sleep bruxism in early childhood. Material and method A cross-sectional observational study carried out with 371 children between 4 and 6 years of age. Parents answered a questionnaire with aspects related to their children's sleep behavior. Among the clinical characteristics, the presence of lip sealing, clicking, teeth marks on the jugal mucosa, and the side of the tongue was evaluated. Tooth wear was assessed using the BEWE index criteria. Simple logistic regression models were adjusted for each independent variable, estimating the gross odds ratios with the respective 95% confidence intervals. Variables with P <0.20 in the individual analyzes were adjusted in a multiple logistic regression model, with those with P ≤ 0.05 remaining in the model. Result 42.4% of parents reported that their children gritted their teeth while sleeping. Children who showed wear on their teeth were 1.53 times more likely to grind their teeth. There was no significant association with the other variables analyzed (P > 0.05). Conclusion Behavioral aspects were not associated with probable sleep bruxism. Among the clinical characteristics evaluated, tooth wear showed an association, which may indicate the probable bruxism of sleep in early childhood.